The Influence of Compensation, Work Environment, Job Satisfaction, and Emotional Intelligence on Employee Performance : A Literature Review - Murwijaya, Indiramukti; Syamsunasir, Syamsunasir (Dinasti International Journal of Management Science, 2025)
This literature study aims to ascertain how employee performance is impacted by compensation, work environment, job satisfaction, and emotional intelligence. This research was conducted between 2020 and 2024. This research will be used to inform future studies in the field of human resource management. Relevant research is very important in research articles, which serves to strengthen the theory of relationships between variables. The objects in this study came from various employee fields, such as state-owned enterprise employees, bank employees, civil servants, and hospital employees. So, the results of research be able to provide input to all institutions, including public companies, private companies, government, and also state-owned enterprise on how to improve employee performance. This research uses quantitative and research with a survey method by giving questionnaires to respondent. Another research use with qualitative research with data collection techniques through in-depth interviews, participant observation, and documentation. The results of this study indicate that work environment, job satisfaction, and emotional intelligence have a directy and positively effect on employee performance. And also, compensation have directly and non-directly effect on employee performance.